2014
DOI: 10.1177/2158244014542776
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of SMEs’ Attitudes and Practices Toward Tax Compliance in Zimbabwe

Abstract: The informal sector has become the major employer in Zimbabwe, but the sector is not contributing meaningfully to the treasury due to noncompliance on tax remittances by the operators. The research was done on 50 businesses in the retail sector in Gweru. The findings are that minimal efforts are being put in place to enforce compliance, and corruption levels are high among the tax collection officials. Small and medium enterprises (SMEs) evade compliance by paying bribes, keeping two sets of records, relocatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 5 publications
6
17
0
Order By: Relevance
“…Penalty in compliance is the process of increasing power of the authorities to ensure enforced compliance (Kirchler, Hoelzl, & Wahl, 2008). Also, Nyamwanza, Mavhiki, Mapetere and Nyamwanza (2014) in their studies revealed that penalty is found to be the most effective variable in enforcing compliance. In addition, other studies conducted on enforce compliance, found that penalty has played a great role to deter, motivate and correct improper behaviour of SMEs (Poppelwell, Kelly, & Wang, 2012;Wenzel, 2001).…”
Section: Penalty Magnitude (Pm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Penalty in compliance is the process of increasing power of the authorities to ensure enforced compliance (Kirchler, Hoelzl, & Wahl, 2008). Also, Nyamwanza, Mavhiki, Mapetere and Nyamwanza (2014) in their studies revealed that penalty is found to be the most effective variable in enforcing compliance. In addition, other studies conducted on enforce compliance, found that penalty has played a great role to deter, motivate and correct improper behaviour of SMEs (Poppelwell, Kelly, & Wang, 2012;Wenzel, 2001).…”
Section: Penalty Magnitude (Pm)mentioning
confidence: 99%
“…In addition, penalties have been found to be the most effective tools in Zimbabwe. As most SMEs evade remitting tax collections by bribing the tax collection officers through keeping two set of records and sometimes relocating to new sites without notifying the tax officials (Nyamwanza et al, 2014). However, Swistak (2016) posits that penalties have the potential to work effective if used as an auxiliary means of delivery and implementing a sound compliance strategy.…”
Section: Penalty Magnitude (Pm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of regulatory authorities are government departments like tax authorities, standards setting, and monitoring boards, environment monitoring boards and local authorities. A considerable number of MSMEs in Zimbabwe face closure every year when the Zimbabwe Revenue Authority fines them heavily for failing to comply with various tax laws of the country (Utaumire, Mashiri & Mazhindu;Nyamwanza, Mavhiki, Mapetere, & Nyamwanza, 2014). Therefore compliance to the country's trade regulations could ensure that an enterprise avoids unnecessary penalties and operate profitably leading to its long term success.…”
Section: Conformance To Regulationsmentioning
confidence: 99%